The interplay between Salmonella and host: Mechanisms and strategies for bacterial survival - Hongyu Zhao; Xinyue Zhang; Ningning Zhang; Li Zhu; Huan Lian (Cell Insight)
Salmonella, an intracellular pathogen, infects both humans and animals, causing diverse diseases such as gastroenteritis and enteric fever. The Salmonella type III secretion system (T3SS), encoded within its pathogenicity islands (SPIs), is critical for bacterial virulence by directly delivering multiple effectors into eukaryotic host cells. Salmonella utilizes these effectors to facilitate its survival and replication within the host through modulating cytoskeletal dynamics, inflammatory responses, the biogenesis of Salmonella-containing vacuole (SCV), and host cell survival. Moreover, these effectors also interfere with immune responses via inhibiting innate immunity or antigen presentation. In this review, we summarize the current progress in the survival strategies employed by Salmonella and the molecular mechanisms underlying its interactions with the host. Understanding the interplay between Salmonella and host can enhance our knowledge of the bacterium's pathogenic processes and provide new insights into how it manipulates host cellular physiological activities to ensure its survival.